INVESTIGATION AND ISOLATION OF MYCORRHIZAL FUNGI FROM TERRESTRIAL ORCHID GENUS SPATHOGLOTTIS GROWN IN POT - Junsri, Theeraporn; Jaiboon, Apsonsawan; Tanruean, Keerati; Poolprasert, Pisit; Sumang, Rattiphorn; Kodsueb, Rampai; Chutima, Ruangwut (PSRU Journal of Science and Technology, 2020)
This research aims to investigate the mycorrhizal relationship and isolate mycorrhizal fungi from terrestrial orchid, genus Spatthoglottis, which grown in pot to use as basically data for development of fungal inoculum and enhancing growth of terrestrial orchid grown in pot. The roots of 3 Spathoglottis orchids were corrected, randomly and stained with 0.05% w/v trypan blue. The results showed that the peloton structures, coil of fungal hypha, were found in cortex root tissues of all 3 orchid plants. In addition, 6 fungal isolates were isolated from roots of these 3 orchid samples and all fungal isolates were able to culture in laboratory without host plant. The fungal morphological study, including of fungal colony on agar media and characterization of hyphaunder microscope, revealed that all fungal isolated belonged to higher fungi due to septate hypha were found. Moreover, 5 fungal isolates were found spore formation after cultured on Potato dextrose agar (PDA) while fungal isolate SPGT 006 was not found spore formation. This research indicated that the mycorrhizal relationship was found in terrestrial orchid, genus Spathoglottis, grown in pot and all isolated fungi were able to culture in laboratory without their host plants. Therefore, these results are possibility for further study to develop mycorrhizal inoculum for terrestrial orchid grown in pot.